2007
DOI: 10.1002/prca.200600618
|View full text |Cite
|
Sign up to set email alerts
|

A method for the selective isolation and enrichment of carrier protein‐bound low‐molecular weight proteins and peptides in the blood

Abstract: The low molecular weight (LMW) region of the circulatory proteome, thought to contain a rich source of biomarkers, resides in vivo, in a complexed state with larger, highly abundant resident proteins. Consequently, serum fractionation approaches that deplete the high-abundance proteins under native conditions will remove much of the LMW proteome. We describe a new strategy to systematically collect, isolate and enrich the LMW molecules that would be otherwise eliminated during the depletion of high-abundance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Accordingly, three LC-MS/MS repeats provide comprehensive identification of the proteins present in the tryptic digested fractions. These results are remarkably better than those reported by Camerini et al which ran a total of eight repeats: three repeats identified about 70% of the proteins, whereas seven repeats were required to identified 98% of the proteins [16]. In the followon experiments, we ran three LC-MS/MS repeats for each fraction of each sample/experiment set.…”
Section: Integration Of the Ram-rp And Be Modulessupporting
confidence: 40%
See 1 more Smart Citation
“…Accordingly, three LC-MS/MS repeats provide comprehensive identification of the proteins present in the tryptic digested fractions. These results are remarkably better than those reported by Camerini et al which ran a total of eight repeats: three repeats identified about 70% of the proteins, whereas seven repeats were required to identified 98% of the proteins [16]. In the followon experiments, we ran three LC-MS/MS repeats for each fraction of each sample/experiment set.…”
Section: Integration Of the Ram-rp And Be Modulessupporting
confidence: 40%
“…Ultrafiltration with 10-30 kDa filters has been used frequently for selective removal of high abundance, larger proteins [11][12][13][14] though some leakage of high molecular weight molecules and great variance in cut-off accuracy has been noted [15]. Electrophoretic methods [16] and size exclusion chromatography [17] also have shown promise in this regard but, similar to ultrafiltration, the small sample load and low throughput have limited their utility in biomarker discovery applications.…”
Section: Introductionmentioning
confidence: 99%
“…The particles were heated in SDS sample buffer for 5 minutes at 100 °C and loaded on a 4-20 % Tris Glicine gel (Invitrogen). Bands below 30 kDa were cut and ingel trypsin digestion was performed 11 . The resulting peptide fragments were analyzed by online liquid chromatography/electrospray ionization tandem mass spectrometry (LC/ESI MS) using LTQ-Orbitrap mass spectrometer (Thermo Fisher).…”
Section: Demonstration Of Isolation and Enrichment Of Low Molecular Wmentioning
confidence: 99%
“…However, due to the complexity and high dynamic range of endogenous peptides and the interference from high concentrations of proteins, salts and lipids in biological samples, the ability to extract peptides/small proteins from the complex biological samples as well as enhancing the sensitivity toward peptides/small proteins at low abundance, remains a great challenging task before MS analysis. Thus, various methods (ultrafiltration [62], solid-phases extraction [63], selective electrophoresis and continuous elution electrophoresis [64], organic solvent precipitation [65]) have been developed to isolate peptides/small proteins before MS analysis. Centrifugal ultrafiltration with accurate MW cutoff is one widely used method for peptide enrichment based on size-exclusion effect.…”
Section: Size-selective Enrichment Of Endogenous Peptides and Proteinsmentioning
confidence: 99%